How Effective is the Use of Digital Evaluation Media in Learning Student: A Review - Safitri, Elza; Purnamasari, Lora (JOURNAL OF DIGITAL LEARNING AND DISTANCE EDUCATION, 2024)
The learning process is monotonous and lacks media and facilities inadequate learning will affect learning outcomes and ways of thinking students. Evaluation is part of the process that is used as a rejection. Lecturer evaluation by giving grades and completeness predicates to students contributes greatly and must be updated along with development factors. One of them is digital evaluation. During the process, learning is evaluated to have found a method that is efficient, acceptable, and makes students enthusiastic and able to complete the next assignment to attract students' interest. This can be achieved by applying technology as a new tool for assessing learning. Researchers achieved research that uses a systematic literature review method, which aims to identify effective digital learning evaluation methods in various journals and research journals on educational evaluation. Next, literature from various databases is interpreted and a review is made about the use and success of digital evaluation media for students and teachers in learning statistics through applications or the web. Therefore, research findings suggest that digital evaluation tools can increase students' interest and desire to learn and use them to greatly help lecturers interactively deliver lessons.